2011
DOI: 10.1254/jphs.10250fp
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase SHP-2 Is Positively Involved in Platelet-Derived Growth Factor–Signaling in Vascular Neointima Formation via the Reactive Oxygen Species–Related Pathway

Abstract: Abstract. The roles of Src homology domain 2-containing protein tyrosine phosphatase 2 (SHP-2) and its signaling in atherosclerosis have not been explored. Therefore, we investigated the roles of SHP-2 in the movement of rat aortic smooth muscle cells (RASMCs) and in the neointima formation of the carotid artery. Platelet-derived growth factor (PDGF)-BB (1 − 20 ng/ml) increased the activity and phosphorylation of SHP-2 and migration in RASMCs and these were suppressed by SHP-2 inhibitor NSC-87877 (30 μM) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that PDGF activation enhanced SHP-2 and PTP1B activity (46,47), which may explain our results. We have reported that activation of PKCδ induces the expression of SHP-1 in cultured pericytes exposed to high glucose concentrations and inhibits the PDGF signaling pathway contributing to pericyte apoptosis (23).…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that PDGF activation enhanced SHP-2 and PTP1B activity (46,47), which may explain our results. We have reported that activation of PKCδ induces the expression of SHP-1 in cultured pericytes exposed to high glucose concentrations and inhibits the PDGF signaling pathway contributing to pericyte apoptosis (23).…”
Section: Discussionsupporting
confidence: 75%
“…SHP-2 is abundant in vascular SMC [41], and its expression levels are elevated upon vascular injury [42], [43]. PDGF-mediated smooth muscle cell migration is inhibited by the SHP-2 inhibitor NSC-87877 and interestingly, oral administration of the SHP-2 inhibitor, NSC-87877 significantly suppressed neointima formation in a rat model of carotid artery injury [44].…”
Section: Discussionmentioning
confidence: 99%
“…In their dimeric form, PDGFs bind to and activate a PDGF receptor (PDGFR) that consists of two receptor tyrosine kinase subtypes, PDGFR-a and PDGFR-b, localized to the plasma membrane of cells. Once bound to a PDGF, PDGFRs activate diverse signaling molecules and regulatory proteins that contain Src homology 2-domains and thereby elicit various cellular responses like actin reorganization, proliferation, differentiation, or VSMC migration (Jiang et al, 2010;Won et al, 2011).…”
Section: Introductionmentioning
confidence: 99%